(untitled) (Itinera, 2023)
By analysing a choice of Carol Rama’s (1918-2015) pictorial works and comparing them with her ‘discursive practices’ or the ways she articulates her verbal expressions and interactions, this paper aims to construe a particular model for studying the relation between words and images, drawn from and inspired by both Émile Benveniste’s ‘Enunciation’ Linguistics and Mikhail Bakhtin’s Metalinguistics. Read in this way, the alleged "pornography" of some of Carol Rama’s early works is transformed into its opposite, that is, into an invitation addressed to a traditional voyeur to become a possible erotic interlocutor. This transformation is effected by the figures appearing in Rama’s paintings, who aim their gaze directly at the spectator’s eyes, addressing him as "you". Instead of enticing a voyeur, stealthily peeping at a sensual object, the figures’ gaze transforms the spectator into a “second person of the enunciation” (Benveniste). Similar considerations apply to Carol Rama’s discursive practices, all of which are characterized by a "polyphony of voices", a polyphonic ensemble whose voices are not split and conflicting against one another. To quote Bachtin’s on Dostoewsky’s characters, whose voices are usually self-conflicting, in Carol Rama’s case, the voices are problematically “pacified” (Bakhtin,).